Blended Learning Untuk Anak Usia Dini di Masa Pandemi Covid-19 - Desi Permasih (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
The purpose of this study was to determine blended learning as a strategy to improve the character of early childhood independence during the COVID-19 pandemic. Since the implementation of learning from home. Blended learning method is the right method to use today, Blended learning is a combination of face-to-face learning and learning that utilizes information technology in its implementation. During this pandemic, children need more knowledge about life skills and character than about academic achievement, so that children have insight into what is happening around them and are able to protect themselves. This study uses a qualitative descriptive method with a literature study design taken from various sources of books, journals, articles and other relevant sources. These sources of data will be compared to draw conclusions. The results show that blended learning can be used as an alternative strategy to improve the character of independence in early childhood during the COVID-19 pandemic. The use of the blended learning method should not only increase the character of independence, other characters so that children grow up to become individuals with character.Keywords: Blended Learning; Bathing Character; Covid19 Pandemic. AbstrakTujuan penelitian ini adalah mengetahui pembelajaran blended learning sebagai strategi untuk meningkatkan karakter kemandirian anak usia dini dimasa pandemic covid-19. Sejak diberlakukan belajar dari rumah. Metode blended learning merupakan metode yang tepat untuk digunakan dimasa sekarang ini, Blended learning merupakan perpaduan antara pembelajaran tatap muka dan pembelajaran yang memanfaatkan teknologi informasi dalam pelaksanaannya. Dimasa pandemic ini anak lebih membutuhkan pengetahuan tentang ketrampilan hidup dan karakter daripada tentang pencapaian akademik, agar anak memiliki wawasan tentang apa yang terjadi disekitarnya dan mampu melindungi dirinya. Penelitian ini menggunakan metode deskriptif kualitatif dengan desain studi literature yang diambil dari berbagaimacam sumber buku, jurnal, artikel dan sumber relevan lainnya. Sumber- sumber ini datanya akan dibandingkan untuk diambil kesimpulan. Hasil penelitian menunjukkan bahwa pembelajaran blended learning dapat digunakan sebagai alternatif strategi untuk meningkatkan karakter kemandirian pada anak usia dini dimasa pandemic covid-19. Penggunaan metode blended learning sebaiknya tidak hanya meningkatkan karakter kemandirian, karakter-karakter lainnya agar anak tumbuh menjadi pribadi yang berkarakter.Kata Kunci: Blended Learning; Karakter Kemandirian; Pandemi Covid 19.